Effect of the Terminal Acceptor Unit on the Performance of Non-Fullerene Indacenodithiophene Acceptors in Organic Solar Cells - Natalia Terenti; Gavril-Ionel Giurgi; Lorant Szolga; Ioan Stroia; Anamaria Terec; Ion Grosu; Andreea Petronela Crișan (Molecules, 2022)
Four acceptor–donor–acceptor (A–D–A)-type molecules bearing indacenodithiophene as donating central core and various end-capping acceptor units have been designed and synthesised as n-type materials suitable for organic solar cells (OSCs). The studied optical and electrochemical properties supported by theoretical calculations revealed that the nature and the strength of the terminal groups exert a decisive influence on the polymer bulk-heterojunction OSC performance.